Faktor – faktor yang berpengaruh terhadap agresivitas pajak - Andika Surya Kusuma; Maryono Maryono (Politeknik Ganesha Medan, 2022)
This study looks at the phenomenon of the tax ratio which shows the government's ability to collect tax revenues. The higher the tax ratio of a country, the better the performance of that country's tax collection. The company carries out aggressive tax planning to save its taxes. This tax savings is known as tax aggressiveness. Tax aggressiveness is an act of manipulating tax able income by a company through tax planning actions, either using legally or illegally classified methods. Another phenomenon is tax avoidance in Indonesia, which is believed to reach Rp 110 trillion per year. Most business entities own about 80 percent, the rest are tax payers for individuals. The purpose of this study was to examine and analyze the effect of Profitability (ROA), Liquidity (CR), Leverage (DAR) and Company Size (SIZE) on Tax Aggressiveness. The samplingmethodused in this research is purposive sampling and obtained a sample of 322 companies. The population in this study were all manufacturingcompanies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The data analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that liquidity, leverage and also company size have a negative and significant effect on tax aggressiveness, while the results of research on profitability do not have a significant effect on tax aggressiveness.